The Significance of Histopathologic Assessment in Bone Marrow Disease in Neuroblastoma - Sumeyye EKMEKCI; Dilek INCE; Nur OLGUN; Erdener OZER (Federation of Turkish Pathology Societies, 2022)
Objective: Neuroblastoma (NB) is the most common extracranial solid tumor in children and is responsible for 12% of cancer-related deaths. The status of metastatic disease in the bone marrow (BM) is a predictor of poor outcome. The purpose of this study was to investigate the predictive significance of histopathological examination of BM in NB. Material and Method: The study included 61 cases with archival bone marrow biopsy tissues. The cases were evaluated regarding the percentage of metastatic tissue and its differentiation. Primary tumor slides were also reviewed to perform the Shimada classification based on the differentiation status and mitosis-karyorrhexis index. The patients' age, gender, NMYC amplification, clinical risk group, and disease outcome were also noted. Results: Of the 61 cases, 17 had BM involvement. Of those, eight cases (47.1%) were refractory NB showing disease relapse. Based on BM examination, five cases (29.4%) were categorized as complete response, seven (41.2%) as progressive disease, three (17.6%) as minimal disease, and two (11.8%) as stable disease. The progressive disease category was significantly related with refractory disease and NMYC amplification along with the high-risk category (p =0.002 and p= 0.003 respectively). Undifferentiated histology and presence of more than 20% of tumor tissue in the BM biopsy at diagnosis were significantly associated with the progressive disease category (p=0.01 and p<0.001, respectively). Conclusion: We conclude that evaluating the percentage of metastatic tumor tissue and tumor differentiation in BM biopsies is of clinical importance in the management of neuroblastoma patients.